Force transmissibility and vibration power flow behaviour of inerter-based vibration isolators - Yang, Jian (IOP Publishing, 2016)
This paper investigates the dynamics and performance of inerter-based vibration isolators. Force / displacement transmissibility and vibration power flow are obtained to evaluate the isolation performance. Both force and motion excitations are considered. It is demonstrated that the use of inerters can enhance vibration isolation performance by enlarging the frequency band of effective vibration isolation. It is found that adding inerters can introduce anti-resonances in the frequency-response curves and in the curves of the force and displacement transmissibility such that vibration transmission can be suppressed at interested excitation frequencies. It is found that the introduction of inerters enhances inertial coupling and thus have a large influence on the dynamic behaviour at high frequencies. It is shown that force and displacement transmissibility increases with the excitation frequency and tends to an asymptotic value as the excitation frequency increases. In the high-frequency range, it was shown that adding inerters can result in a lower level of input power. These findings provide a better understanding of the effects of introducing inerters to vibration isolation and demonstrate the performance benefits of inerter-based vibration isolators.